Two‐year follow‐up of donors in a large national study of ferritin testing. Issue 12 (27th September 2018) - Goldman, Mindy; Uzicanin, Samra; Osmond, Lori; Yi, Qi‐Long; Scalia, Vito; O'Brien, Sheila F.
Abstract : BACKGROUND: We assessed donor return rates, donation frequency, and factors related to the evolution of ferritin levels 2 years after entering donors into a large operational study of ferritin testing. STUDY DESIGN AND METHODS: Ferritin testing was done on donors from representative clinics (n = 12, 595). Low‐ferritin donors (<25 μg/L) were informed and not called for 6 months to book a donation. Approximately 37% of donors had ferritin retested on a return donation. Return rate and donation frequency were monitored, and a logistic regression model was constructed. RESULTS: The return rate was lower in low‐ferritin donors (67% vs. 78%), particularly in women who were first‐time donors (36% vs. 61%). Returning low‐ferritin donors made fewer donations in the 2 years after notification compared to the 2 years prenotification (4.5 vs. 7.5 for men, 3.0 vs. 5.0 for women), while donation frequency was lower and increased slightly for normal‐ferritin donors (4.7 vs. 4.4 for men, 3.6 vs. 3.1 for women). An increased number of donations, shorter interdonation intervals, female sex, and younger age are associated with low ferritin levels on initial and repeat testing. Some recovery of ferritin occurred, but most low‐ferritin donors continued to have low or borderline levels on retesting. CONCLUSION: Informing donors of low ferritin results had a long‐lasting impact on return rates and donation frequency, requiring recruitment efforts to maintain adequacy of supply. Increasing the interdonation interval leads to some improvement in ferritin levels; more sustained efforts to encourage donors to improve iron intake are needed to achieve long‐term benefit.